ANALYSIS OF NEOLOGISMS IN MEDIA DISCOURSE FROM LINGUO PRAGMATIC ASPECT (Archive of Conferences, 2021)
This thesis is dedicated to the analysis of neologisms in mass-media discourse. Language functions in the society which develops and evolves as a system. The society persistently needs support in the language and the reflections in the changes which motivates linguistic progressions. Neologisms in mass-media is of peculiar interest to scholars as a word in this sphere of life should possess expressiveness, draw the attention of the audience. So lexical units capable of fulfilling a certain communicative task are shaped. And it is the mass-media that spreads these new words and is the means of their popularization. It is noted that by means of verbal evaluations the reflection of a language personality in a lexico-semantic system takes place. The thesis highlights that the analysis of new words contributes to the understanding of typical and specific peculiarities of a people by a language personality.